Increasing the Capacity of Paud Teachers with Training of Educators on School Health Business Activities in Early Children Education Park in Marelan City - Rusdiana, Rusdiana; Widjaja, Sry Suryani; Amelia, Rina; Rusmalawaty, Rusmalawaty; AA, Rizka; Y, Devi; C, Teguh; W, Steven; EM, Samuel (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2023)
Improve healthy and clean-living behavior starting from early childhood, this can affect the growth and development of children and also the level of intelligence of children to produce a healthy and quality generation. The North Sumatra Kahmi Amanah Playgroup where early childhood education is located in the Medan Marelan area is a potential place that should be developed for early childhood education. School Health Business Activity is an activity that can foster clean and healthy behavior from an early age in children in the surrounding area who are children around Marelan area. The community service team funded by the University of North Sumatra through the LPPM institution consisting of lecturers from the Faculty of Medicine with different departments and also lecturers from the Faculty of Public Health is engaged in providing training to improve the skills of educators for school health business activities as well as providing medical equipment and facilities. needed and not yet available in the Amanah Kahmi playgroup, such as closed trash cans, making hand washing sinks, and thermogenic so that this community service activity can produce something useful for the community around the Medan Marelan area.